Classic lattice corneal dystrophy associated with monoclonal gammopathy following exclusion of a TGFBI mutation - Mohd. Kamal, Khairidzan; Rayner, Sylvia A.; Chen, Michael C.; Aldave, Anthony J. (Lippincot William @ Wilkins, 2009)

(untitled)
Purpose To report the association of phenotypic features characteristic of lattice corneal dystrophy with a monoclonal gammopathy of undetermined significance following exclusion of a coding region mutation in TGFBI.